2012
DOI: 10.1021/ie301524r
|View full text |Cite
|
Sign up to set email alerts
|

Quaternary Ammonium “Tannate” for Antifouling Coatings

Abstract: The undesirable accumulation of a wide variety of marine organisms (biofouling) on ship hulls can lead to significantly increased costs, principally by increased fuel consumption to maintain cruising speed. Generally, these coatings have bioactive compounds, called biocides. In this sense, this paper deals with the assessment of the antifouling properties of a natural product derivative obtained from "quebracho" tannin and a quaternary ammonium salt (hexadecyltrimethylammonium bromide ([CH 3 (CH 2 ) 15 N(CH 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…Indeed, we observed that the addition of small amounts of ammonia to TA in ethanol leads to precipitation, likely due to the formation of ammonium tannate. 43 We found that with TEOS as precursor under these conditions, nonporous silica particles are formed. On the other hand, when large amounts of ammonia are added to TA in ethanol, a red solution is formed.…”
Section: ■ Results and Discussionmentioning
confidence: 79%
“…Indeed, we observed that the addition of small amounts of ammonia to TA in ethanol leads to precipitation, likely due to the formation of ammonium tannate. 43 We found that with TEOS as precursor under these conditions, nonporous silica particles are formed. On the other hand, when large amounts of ammonia are added to TA in ethanol, a red solution is formed.…”
Section: ■ Results and Discussionmentioning
confidence: 79%
“…We suggest that these are likely to include invasive organisms in a mechanism similar to transport on the hulls of ships. [22,23] Perhaps other consequences associated with these anthropogenic plastic particles await discovery.…”
Section: Discussionmentioning
confidence: 99%
“…Products obtained from plants stand out like polyphenolic and terpenic compounds. In the case of polyphenolic compounds, this has been applied mostly in antifouling and anticorrosive paint formulations with promising results [111,112]. Essential oils are widely studied because of their antibacterial and antifungal activity to be applied to surface treatments by thin layers; some examples of this are those obtained from anise, garlic, cinnamon, oregano, and clove essential oils [113e116].…”
Section: Inorganic and Organic Compounds With Antimicrobial Potentialities To Coatingsmentioning
confidence: 99%